Effects of glucosamine and chondroitin sulfate supplementation in addition to resistance exercise training and manual therapy in patients with knee osteoarthritis: a randomized controlled trial - Muhammad Osama; Babur, Muhammad Naveed; Siddiqi, Furqan Ahmed; Tassadaq, Naureen; Tareen, Muhammad Ali Arshad (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the added benefits of short-term glucosamine and chondroitin sulfate supplementation in combination with manual therapy and resistance exercise training in the management of knee osteoarthritis. Method: The parallel-design, double-blind randomised controlled trial was conducted from January to September 2020 at the Foundation University Institute of Rehabilitation Sciences and Fauji Foundation Hospital, Rawalpindi, Pakistan, and comprised knee osteoarthritis patients of either gender having radiological evidence of grade III or less on Kellgren classification. The subjects were randomly allocated experimental group A and control group B. Both the groups received manual therapy and resistance exercise training, while group A additionally received glucosamine and chondroitin sulfate supplementation for 4 weeks. Study outcomes included pain, function, quality of life, range of motion, strength, fall risk, skeletal muscle mass, visceral fat area, body fat, intracellular water ratio, and segmental lean and fat mass. Data was analysed using SPSS 21. Results: Of the 24 subjects, there were 12(50%) in each of the two groups. Both groups had 9(75%) men and 3(25%) women. In terms knee osteoarthritis grade, there was no significant difference between the groups (p=1.00). No significant differences were observed in any of the outcome measures neither at the halfway mark, nor post-intervention between the groups (p>0.05) except for percentage change in segmental lean mass of the right leg at the 2nd week and of the left leg at the 4th week (p<0.05). ---Continue